An Advanced Surgical Dressing for High-risk Patients Undergoing Breast Cancer Surgery: A Case-control Study. Issue 11 (November 2021) - Nicotera, A.; Ferrando, P.M.; Ala, A.; Brunetti, M.; D'Anna, M.R.; Passera, R.; Malan, F.
Abstract : Background: Oncological breast surgeries, classified as breast conserving surgery, oncoplastic surgery, and mastectomies (standard or with tissue sparing and reconstruction), are burdened with an overall complication rate up to 33%. Aquacel Ag Surgical is a combined hydrofiber-hydrocolloids dressing. The aim of this study is to evaluate the incidence of surgical site complications in patients presenting with three or more risk factors (or two, of which at least one classified as "high risk"), undergoing breast cancer surgery with/without reconstruction, comparing advanced (Aquacel Ag Surgical) with traditional dressing. Methods: This is a retrospective, monocentric, case-control study based at the breast unit of the Città della Salute e della Scienza Hospital of Turin, Italy. Forty-two patients who underwent breast surgeries and met the inclusion criteria were enrolled, from February 1 to July 31, 2018. The primary endpoint was comparing the incidence of surgical site complications (skin alterations, infection, and wound dehiscence) in the two groups. The secondary endpoints were evaluating patient's quality of life, aesthetic outcomes, and compliance to the dressings. Results: The distribution of risk factors at the baseline between the two groups was balanced, without statistically significant differences. Wound complications' incidence at 1 week was lower in the advanced dressing group ( P = 0.015). On the bivariate descriptive analysis, advanced dressing proved to be easier to remove for the operator ( P = 0.026). The aesthetic outcomes vouched for better scores in the advanced dressing group. Conclusion: In the presented study Aquacel Ag Surgical dressing reduces surgical site complications in the first week after surgery in patients affected by three or more risk factors (or two with at least one classified as "high risk").